Indústria brasileira do gás natural: a lei do gás e os conflitos legais e regulatórios entre a União Federal e os Estados - Gonçalves, Gustavo Mano (2010)
This dissertation has the objective to study certain conflicts between the agents of the Brazilian natural gas industry originated from the singular model adopted by the Federal Constitution. According to such model the Federal Government has the monopoly and the authority to legislate and regulate the exploration, production, importation, exportation and transportation by pipelines of the natural gas, while the States shall explore the local distribution services. This duplicity of attributions has given rise to some administrative and legal conflicts evidencing a lack of legal stability in the Brazilian natural gas sector, inhibiting investments in the relevant industry. It is also analyzed the fundamentals of said conflicts and the repercussion of the Gas Law nr. 11,909/09 in the solution or reduction of these conflicts and the paper of the States in the stabilization of the legal and regulatory framework of the Brazilian gas industry. Qualitative and critical-dialectic research method was adopted together with case studies and bibliography surveys. The research is divided in two stages: in the first one a description of the natural gas industry is presented, with an analysis of the main regulatory systems adopted in the world, including the Brazilian system; the second stage contains the study of some cases of regulatory conflicts in Brazil, as well as an analysis of the ways by which, based on the Gas Law, the state and private agents can contribute to reduce or eliminate these conflicts and confer legal stability to the Brazilian industry of the natural gas. As a result of the work there is a need for the agents of the natural gas industry in Brazil to develop tools for collaboration and cooperation, especially in order to structure and implement efficient and effective regulatory agencies, particularly within the States, final stage of this economic chain, with the product being delivered to end users.